Ginga-NCL: the declarative environment of the Brazilian digital TV system - Soares,Luiz Fernando Gomes (2007)
As in all main terrestrial DTV Systems, the Brazilian middleware, named Ginga, supports both declarative applications (through its presentation, or declarative, environment Ginga-NCL) and procedural applications (through its execution, or procedural, environment Ginga-J). Since hybrid applications are common, either type of Ginga application may make use of facilities of both presentation and execution application environments. This paper focuses on the presentation environment Ginga-NCL. The main Brazilian inovations are then presented, regarding the Ginga architecture, the declarative NCL language specification, the editing commands for live application production, and the transport data structure.